ӨЛШЕМ ТҮСИНИГИНЕ ҚАТНАСЛЫ СОМАТИКАЛЫҚ ФРАЗЕОЛОГИЗМЛЕР - Шынназарова, Саодат Жубатхановна (FAN va JAMIYAT, 2026)
The article discusses the issue of measurative somatic phraseological units in Turkic linguistics, including Karakalpak linguistics. He paid attention to the use of mesurative somatic phraseological units in Karakalpak literary works. Explanations of their meanings are provided in phraseological dictionaries of the Karakalpak language.